MONETARY ALLOWANCE OF MILITARY PERSONNEL OF THE LEADING NATO MEMBER COUNTRIES AND UKRAINE: COMPARATIVE ANALYSIS - Городянська, Л.В. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2023)
The article provides a comparative analysis of the models of monetary allowance systems for military personnel of the leading NATO member countries and Ukraine for further formation of an effective model of the monetary allowance system for military personnel of the Armed Forces of Ukraine. The criteria for the selection of a number of leading NATO member countries for a comparative analysis of models of monetary allowance systems for military personnel have been defined and substantiated, namely, the largest total number of armed forces, financial expenditures for the armed forces, and expenditures for defense needs as a percentage of GDP. Based on these criteria, a group of NATO member countries was formed on a continental basis: North America, Great Britain, and Europe. A detailed analysis of NATO countries' defense expenditures as a percentage of GDP in the period before the beginning of the Russo-Ukrainian war and during full-scale Russian armed aggression was carried out. The principles of formation and functional components of the monetary allowance systems of military personnel of the studied NATO member countries are defined and analyzed, the main of which is basic salary, which takes into account the military rank, years of service, and the corresponding payment grade and additional payments. The procedure and amount of monetary allowance for military personnel of the Armed Forces of Ukraine, the calculation of which depends directly on the serviceman's participation in combat operations and on his performance of combat tasks is given. Based on the conducted analysis, common features were established and a generalized model of monetary allowance systems of the leading NATO member countries and Ukraine was built. It is claimed that such a model can be used as a basis for the development of a perspective system of monetary allowance for military personnel of the Armed Forces of Ukraine according to the scheme "pay for military rank according to the level of responsibility on the position - payment for years of service in a military rank - additional payments and allowances for skills and conditions of service" taking into account the principles of the state-wide labor remuneration system. The study showed that the average salary in the country could be a fundamental indicator in the formation of a new model of the monetary allowance system for military personnel of the Armed Forces of Ukraine.

У статті проведено порівняльний аналіз моделей систем грошового забезпечення військовослужбовців провідних країн-членів НАТО й України для формування в подальшому ефективної моделі системи грошового забезпечення військовослужбовців Збройних Сил України. Визначено й обґрунтовано критерії відбору низки провідних країн-членів НАТО для порівняльного аналізу моделей систем грошового забезпечення військовослужбовців, а саме, найбільша загальна чисельність збройних сил, фінансові витрати на збройні сили та витрати на оборонні потреби у відсотках від ВВП. За цими критеріями сформовано групу країн-членів НАТО за континентальною ознакою: Північна Америка, Велика Британія, Європа. Здійснено детальний аналіз оборонних витрат країн НАТО у відсотках від ВВП у період до початку російсько-української війни й під час повномасштабної російської збройної агресії. Визначено й проаналізовано принципи формування й функціональні складові систем грошового забезпечення військовослужбовців досліджуваних країн-членів НАТО, основними з яких є базовий оклад, що враховує військове звання, вислугу років і відповідний ранг оплати, та додаткові виплати. Приведено порядок і розмір грошового забезпечення військовослужбовців Збройних Сил України, нарахування якого безпосередньо залежить від участі військовослужбовця у бойових діях та від виконання ним бойових завдань. На основі проведеного аналізу встановлено спільні риси та побудовано узагальнену модель систем грошового забезпечення військовослужбовців провідних країн-членів НАТО й України. Стверджується, що таку модель можна покласти в подальшому в основу розробки перспективної системи грошового забезпечення військовослужбовців Збройних Сил України за схемою «оплата за військове звання відповідно до рівня відповідальності за посадою – оплата за вислугу років у військовому званні – додаткові виплати і надбавки за вміння та умови служби» з урахуванням принципів загальнодержавної системи оплати праці. Дослідження показало, що фундаментальним показником при формуванні нової моделі системи грошового забезпечення військовослужбовців Збройних Сил України може стати середня заробітна плата в країні.
ГРОШОВЕ ЗАБЕЗПЕЧЕННЯ ВІЙСЬКОВОСЛУЖБОВЦІВ ПРОВІДНИХ КРАЇН НАТО Й УКРАЇНИ: ПОРІВНЯЛЬНИЙ АНАЛІЗ
Keywords: військовослужбовці; система грошового забезпечення; країни-члени НАТО; модель; базовий оклад; додаткові виплати; військове звання; вислуга років; середня заробітна плата; military personnel; monetary allowance system; NATO member countries; model; basic salary; additional payments; military rank; years of service; average salary